(untitled) (Olhares, 2020)
This article reflects on Stanislavski’s theatrical grammar, regarding its pedagogical application in the theater school Célia Helena since the 70s. It presents a historical contextualization of Stanislavski’s work as of the formulations of his System. It is intended to discuss the creative paths and also the structural knowledge developed by Russian actor and director, which are considered fundamental references within the field of the Performing Arts, from the beginning of the 20th century until today.